Introduction: The portability of care in an increasingly mobile world: chains, drains and circulation - Sònia Parella Rubio (Papers, 2016)
This symposium offers a critical discussion of the logics and dynamics behind the new ‘care circulation’ perspective offered by Loretta Baldassar and Laura Merla in their edited volume entitled “Transnational Families, Migration and the Circulation of Care: Understanding Mobility and Absence in Family Life”. The different contributions to this symposium reflect in particular on the complementarities (or incompatibilities) between two visions of the mobilities of care: a ‘care chains’ approach located in a global economy perspective, and a multi-dimensional approach of the ‘circulation of care’ from a socio-anthropological perspective of family caregiving, located in kinship and the moral economies of care.